A construção de fornos de baixo custo para queimas cerâmicas em alta temperatura: um percurso alternativo possível - Silva, Kleber José da [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Este trabalho se propõe a desenvolver fornos cerâmicos de baixo custo financeiro, com capacidade de alcançar patamares térmicos acima de 1200°C. Tal motivação parte de uma constatação observada, tanto na bibliografia sobre o tema e mercado, de um senso comum ratificador do uso de materiais refratários e isolantes industrializados, como única forma, ou forma ideal para se construir equipamentos capazes de atingir ou superar tal patamar térmico. Por mais que tomemos como base para o desenvolvimento deste estudo, características socioculturais e geográficas específicas de uma região (microrregião de São João Del Rei –MG, Brasil), elas se assemelham à realidade de muitos outros rincões do país, por este motivo acreditamos poder ele servir de ponto de partida para o desenvolvimento de experimentações na área da construção de fornos em outras localidades, valorizando e fortalecendo o intercâmbio de conhecimento entre diferentes culturas, contribuindo com a dimensão extensionista desta pesquisa. O foco no baixo custo de produção dos fornos se dá em função da associação de dois dados: a baixa renda per capita da maior parte da população regional e o alto valor destes equipamentos atualmente disponíveis no mercado, fato que limita o desenvolvimento da vertente da cultura ceramista conhecida como Cerâmica de Alta Temperatura.

This work proposes to develop ceramic kilns of low financial cost capable of reaching above 1200 ° C. The motivation of this work is based on the fact that both in specialized bibliography and in the market, there is a common sense that says the use of refractory materials and industrialized insulation are the only way, or the ideal way, to build equipment capable of reaching or surpassing this thermal threshold. Although we take specific socio-cultural and geographical characteristics of a specific region (micro-region of São João Del Rei - MG) as a basis for the development of this study, we are convinced that they resemble the reality of many other corners of the country. Thus, we believe It can serve for the development of experiments in furnace construction in other localities, valuing and strengthening the exchange of knowledge between different cultures, contributing to the extensionist dimension of this research. The focus on the low cost of furnace’s production is due to the association of two data: the low per capita income of most of the population and the current high value of these equipment available in Brazilian Market. In our understanding, this fact limits the development of the ceramist culture known as Cerâmica of High Temperature in national territory. In its structure, this work is divided in three segments: the first (chapter I) relates to the history of ceramic kilns’ development; In the second (Chapter II) we seek to highlight the importance to the development of the ceramist culture of High Temperature of alternative and low cost furnaces construction; at least (Chapters III and IV) we bring concrete elements that present alternative ways to the production of refractory and insulation materials, as well as three different successful projects of low-cost furnaces for high-temperature firing, whose construction structure is diagrammatically exemplified in the Instructional technique script attached to the end of the work
The construction of low-cost furnaces for high-temperature ceramic burnings: a possible alternative path
La construcción de hornos de bajo costo para disparos cerámicos en alta temperatura: una posible ruta alternativa
Keywords: Cerâmica de alta temperatura; Fornos cerâmicos; Tijolos refratários; Cunha; Tijolos isolantes